Analysis Of Factors Affecting Recurrence People With Mental Disorders - Insiyah Insiyah; Endang Caturini Sulistyowati ((JKG) Jurnal Keperawatan Global, 2022)
Background: Currently around 450 million people worldwide suffer from mental disorders. Patients with mental disorders one third live in developing countries. Riskesdas (2018) found that there was an increase in national psychosis/schizophrenic sufferers (7 per mil). The results of the 2019 study showed that patient relapses were still found which were generally caused by drug withdrawal factors, lack of family support, negative community stigma, and underutilization of health facilities. This study aims to analyze the factors that influence recurrence in people with mental disorders Methods: This study uses a descriptive correlational method, namely research that seeks the relationship between variables. This study utilizes a cross-sectional methodology which is a sort of exploration that underlines the hour of estimation/perception of information on autonomous and subordinate factors at a specific time Results: The majority of respondents were male, as many as 87 (60%), graduate from elementary and non-school, reaching 69 (48.3%). A total of 91 (63.6%) respondents were not working and as many as 89 (62.2%) were single. There was a critical negative connection between self-efficacy and relapse of people with mental disorders (Rs = - 0.414, p = 0.000). There was a positive connection between dysfunctional attitudes and relapse of people with mental disorders (Rs = 0.343, p = 0.000). There was a significant positive relationship between life satisfaction and symptoms of recurrence in patients with mental disorders (Rs = 0.346, p = 0.000). There was a significant positive relationship between social support and symptoms of mental disorder recurrence (Rs = 0.753, p = 0.000). There was a significant positive relationship between medication adherence and relapse in patients with mental disorders (Rs = 0.294, p = 0.000). Adherence to taking medication was an indicator of recurrence in patients with mental disorders with p = 0.000 and OR = 22. Conclusion: Self-efficacy, dysfunctional attitudes, life satisfaction, social support, and medication adherence affect the relapse of people with mental disorders. Appropriate action to the main factors that influence recurrence can be taken to prevent recurrence of patients with mental problems.